2021
DOI: 10.3390/ijerph18094530
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Feasibility of Providing a Family Skills Intervention, “Strong Families”, for Refugee Families Residing in Reception Centers in Serbia

Abstract: War exposure and forced displacement threatens the wellbeing of caregivers and their children, leaving them at risk of negative outcomes, such as elevated rates of anxiety, depression and post-traumatic stress disorder. The importance of engaged, responsive and stable parenting for positive child wellbeing has been documented across diverse cultural and economic backgrounds. Despite the higher need for caregivers to be nurturing in challenging settings, they struggle to provide adequate support for their child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…This study further expands the knowledge cumulated from previous single arm pilots of the Strong Families programme pilot in Afghanistan and with Afghan refugees in Serbia [ 38 , 39 ]. The previous studies indicated positive feasibility and potential effectiveness of the programme on mental health, parenting and family adjustment indicators on families living in stressful situations.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…This study further expands the knowledge cumulated from previous single arm pilots of the Strong Families programme pilot in Afghanistan and with Afghan refugees in Serbia [ 38 , 39 ]. The previous studies indicated positive feasibility and potential effectiveness of the programme on mental health, parenting and family adjustment indicators on families living in stressful situations.…”
Section: Discussionsupporting
confidence: 69%
“…The standardized FDQ had been previously used in other country contexts, such as Afghanistan [ 38 ], Uzbekistan, Zanzibar, Serbia [ 39 ], the Philippines, and the Dominican Republic, and only minor changes in some of the questions were made to reflect the Iranian context. Our aim to collect demographic questions was to perform stratified analyses, as indicated in the aims of our study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations